Adaptation of the forecasting system to control Black Leaf Streak Disease of banana in the specific conditions of Dominican Republic. (13th June 2014) - Guillermet, Claire; Le Guen, Roxane; Foure, Eric; Cespedes, Carlos; De Lapeyre De Bellaire, Luc
Abstract : Introduction . Black Leaf Streak Disease (BLSD) is the most important foliar disease affecting banana production worldwide. A forecasting system has been developed and implemented in various countries aiming at optimal control of BLSD through minimum applications of fungicide. In Dominican Republic, favorable dry climatic conditions contrast with serious organizational issues for BLSD control. Our objective was to evaluate the adaptation of this forecasting strategy in these specific conditions.Materials and methods . Fungicide resistance analyses were carried out in the northwestern region of Dominican Republic, in order to determine the appropriate spectrum of systemic fungicides for the forecasting strategy. Three field experiments were set up on commercial farms where disease evolution was monitored every week, on reference plots, in order to decide the pertinence of fungicide applications.Results . Fungicide resistance to QoI fungicides and strong sensitivity reduction to DMI (Demethylation Inhibitor) fungicides were detected in all farms. In spite of these limitations in the use of some fungicide groups, disease control was achieved with a limited number of fungicide applications (6–9), as compared with 13–26 applications in most commercial farms of Dominican Republic over the same period.Discussion . The calculation of an indicator of the efficiency of the chemical control confirmed the potential of the forecasting strategy, underlining the influence of crop management as well as the neighboring environment of the farms on its efficiency. The requirements for further generalization of this system to commercial farms of this country are discussed.